Hypertrophic Obstructive Cardiomyopathy: Comparison of Outcomes After Myectomy or Alcohol Ablation - Meng, Xiangbin; Wang, Wen-yao; Gao, Jun; Zhang, Kuo; Zheng, Jilin; Wang, Jing-jia; Liu, YuPeng; Shao, Chunli; Tang, Yi-Da (Frontiers in Cardiovascular Medicine, 2022)
Introduction and Objectives The risk of ventricular arrhythmia and heart failure in patients with hypertrophic obstructive cardiomyopathy (HOCM) is much higher than that in the general population. More and more pieces of evidence showed that HOCM is the leading cause of sudden cardiac death in young people. We reported our experience in a study, comparing surgical myectomy, alcohol septal ablation (ASA), and medical therapy. Methods The original cohort included 965 consecutive patients with HOCM. The patients were divided into three groups according to treatment strategies: myectomy group (n = 502), ASA group (n = 138), and medical treatment group (n = 325). The median follow-up duration was 42.99 ± 18.32 months, and the primary endpoints were all-cause mortality and heart transplantation. Results Both in short- and long-term observations, surgical myectomy reduced the left ventricular outflow tract (LVOT) gradients more effectively (7 days, 16.15 ± 12.07 mmHg vs. 42.33 ± 27.76 mmHg, p < 0.05; 1 year, 14.65 ± 13.18 mmHg vs. 41.17 ± 30.76 mmHg, p < 0.05). Among the three groups, the patients in the medical treatment group were at a higher risk of mortality and cardiac transplantation (vs. the myectomy group, p < 0.001 by log-rank test; vs. the alcohol septal ablation group, p = 0.017 by log-rank test), and the myectomy group shows a lower risk of reaching the primary endpoint than the two other groups. In the multivariate Cox regression analysis, previous atrial fibrillation (AF), N terminal pro B type natriuretic peptide (NT-pro-BNP), and surgical myectomy predicted an HOCM prognosis. However, the impact of surgical myectomy on HOCM prognosis seems to be limited to the <56 years group. Conclusions The patients with medical treatments seemed to suffer from the highest risk of achieving an all-cause mortality and the endpoint of heart transplantation. In the long-term survival and clinical outcome, myectomy seemed better than alcohol septal ablation, especially the younger patients. Due to the less-controllable degree, periprocedural complication frequency after alcohol septal ablation was higher, compared with myectomy. Furthermore, gradients after myectomy are lower at late follow-up. To sum up, when selecting treatment strategies, the patients should be individually evaluated by a multidisciplinary team of cardiologists and surgeons.